2019
DOI: 10.1142/s021945541950130x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Analysis for Bending, Buckling and Post-buckling of Nano-Beams with Nonlocal and Surface Energy Effects

Abstract: The modeling and analysis for mechanical response of nano-scale beams undergoing large displacements and rotations are presented. The beam element is modeled as a composite consisting of the bulk material and the surface material layer. Both Eringen nonlocal elasticity theory and Gurtin–Murdoch surface elasticity theory are adopted to formulate the moment–curvature relationship of the beam. In the formulation, the pre-existing residual stress within the bulk material, induced by the residual surface tension in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For this simulation, the applied compressive load is increased incrementally until the start of buckling in the column, Subgraph (e) of Figure 3. Nonlinear buckling analysis involves the application of Newton-Raphson, to solve an iterative and numerical system of equations with strong nonlinearity [21]. Nonlinear buckling is a more realistic simulation than linear buckling, providing a lower buckling load.…”
Section: Numerical Methods Applied To Fixed-free End Shs Columns In C...mentioning
confidence: 99%
“…For this simulation, the applied compressive load is increased incrementally until the start of buckling in the column, Subgraph (e) of Figure 3. Nonlinear buckling analysis involves the application of Newton-Raphson, to solve an iterative and numerical system of equations with strong nonlinearity [21]. Nonlinear buckling is a more realistic simulation than linear buckling, providing a lower buckling load.…”
Section: Numerical Methods Applied To Fixed-free End Shs Columns In C...mentioning
confidence: 99%
“…After considering a variety of boundary conditions, Kiani [43] examined the post-buckling behavior of slender elastic nanobeams, such as simply supported, clamped, and cantilever beams, and discussed the effects of nonlocal parameters, nanobeam length and diameter on the post-buckling of nanobeams under different boundary conditions. Several studies have neglected the effect of initial residual stresses within the material when analyzing the Gurtin-Murdoch surface effect, which was addressed by Nguyen et al [44]. The nonlinear buckling and postbuckling problems of nanobeams were studied using a nanobeam model that included surface effects and residual stresses, and used the Newton iterative method and the solution method of selected integrals.…”
Section: Buckling and Vibration Of Nonlocal Micro-/nano-beamsmentioning
confidence: 99%
“…Also, it was indicated that the size-dependent effects diminish the static large deflections of the bilayer graphene sheet. Nonlinear bending/buckling/post-buckling behavior of the nanobeams using nonlocal elasticity as well as Gurtin-Murdoch surface elasticity energy influences was examined by Nguyen et al [393]. They adopted the preresidual stress produced in the bulk material, enforced by the residual surface tension that happened in the material layers.…”
Section: Nonlinear Static Bending Of Micro/nano-structuresmentioning
confidence: 99%